PAULO FREIRE: ANCHOR, GUIDE, INSPIRATION AN RESOURCE - Arlette Ingram Willis (Associação Brasileira de Alfabetização, 2018)
This study is part of a larger study conducted over four months, about the life and work of Paulo Freire at one university in Rio Grande do Sul. The research question is: How have Freire's ideas and methods influenced education in RS, historically and contemporaneously, in the 21st Century? The qualitative study includes five semi-structured interviews with community activist, graduate student, university administrator, and university faculty members. The interviews lasted 60-90 minute and were conducted in English or Portuguese. Short descriptive narratives of each participant are crafted and extended by field and observation notes. An iterative approach is used and three themes emerged: personal, foundational, and intergenerational. The study reveals, Paulo Freire remains relevant.